The institute of intellectual property in the context of digitalization while ensuring innovative security and human rights - Brovka, Gennady M.; Kandrichina, Irina N.; Veremeychik, Olga V. (Journal of the Belarusian State University. International Relations, 2020)
The article deals with the problem of the functioning of the institute of intellectual property in the context of digitalization challenges, with regard to the necessity of ensuring innovation security and respect for human rights. In the context of digital reality, mechanisms for creating, using, and protecting intellectual property are becoming particularly relevant, and intellectual property itself is positioned as a source of economic and innovative development. The aim of the study is to analyze the functioning of the institute of intellectual property in the frame of digitalization, the need to ensure innovative security and human rights. Implementation of the research goal was achieved through the integrated use of methods of system and comparative analysis, systematization and formalization, historical and statistical methods. The transformation of the institute of intellectual property is considered in the context of the main objectives of the strategy of the Republic of Belarus in the field of intellectual property for 2012–2020. Risks and dominants of the development of the system of protection of intellectual property rights in the context of human rights and digitalization of society are identified.